Heart failure in chronic kidney disease patients: a summary of non-traditional risk factors - Viveiros,Luísa (2018)
Introduction: Patients with chronic kidney disease are at higher risk of heart failure than the general population. Such increased risk is multifactorial, being partly due to a higher prevalence of traditional cardiovascular risk factors in this population and to the existence of non-traditional/chronic kidney disease-specific risk factors. Non-traditional risk factors should prompt special considerations in diagnosis and management of heart failure in these patients. Material and methods: We searched PubMed and Medline during 2017 and 2018, for the terms Chronic kidney disease and Heart failure. Other search terms were included according to the content found. We mainly focused on publications concerning chronic kidney disease-specific risk factors for heart failure and its pathophysiology. Further publications regarding management of heart failure in chronic kidney disease patients were sought. Results and discussion: Heart failure is an important cardiovascular complication in chronic kidney disease. Specific risk factors for heart failure, which are not often found in the general population, include, among others, mineral bone disease, uremic toxins, neuro-hormonal activation, inflammation, oxidative stress, anemia, malnutrition, albuminuria and hyperhomocysteinemia. Management of heart failure in this group of patients is challenging and patients are often undertreated. Conclusion: Research into non-traditional risk factors for heart failure in chronic kidney disease patients is lacking and its pathophysiology is not properly understood. Such understanding is vital to provide proper care, as in the general population. We also question whether some of these specific risk factors could also play a role in heart failure among the general population.